How do programmes to prevent intimate partner violence among the general population impact women with disabilities? Post-hoc analysis of three randomised controlled trials - Andrew Gibbs; Esnat Chirwa; Kristin Dunkle; Erin Stern; Ingrid Van Der Heijden; Laura Washington (BMJ Global Health)
Introduction Women with disabilities experience higher rates of intimate partner violence (IPV) than women without disabilities. There remains limited evidence about whether IPV prevention interventions for the general population have benefits for women with disabilities that compare to those for women without disabilities. Using data from IPV prevention randomised controlled trials in diverse locations (Rwanda, South Africa and Afghanistan), we assess whether outcomes differed by disability status.Methods We assessed disability at baseline in three IPV prevention trials. We performed post-hoc analysis of intervention impacts at endline (22 or 24 months post-baseline) stratified by disability status at study baseline and tested an interaction term for disability at baseline by intervention arm for three sets of outcomes: (1) past year experiences of physical, sexual and severe IPV; (2) economic and livelihood outcomes; and (3) health, mental health and substance use outcomes.Results At baseline between 17.7% and 26.2% of women reported being disabled. For IPV prevention, in seven out of eight tests across three studies, women with and without disabilities had similar outcomes. For economic, health and substance use outcomes, there was more variation, with women with disabilities reporting both better and worse outcomes than women without disabilities; however there was no clear pattern in these differential results.Conclusion IPV prevention programmes targeting general populations can prevent IPV among women with disabilities participants with benefits that mirror those for women without disabilities. Benefits for participants with and without disabilities on secondary programme outcomes related to economic empowerment and health may be more varied and should be explicitly monitored.